2008
DOI: 10.1242/dev.020842
|View full text |Cite
|
Sign up to set email alerts
|

Two highly related regulatory subunits of PP2A exert opposite effects on TGF-β/Activin/Nodal signalling

Abstract: Summary We identify Bα (PPP2R2A) and Bδ (PPP2R2D), two highly-related members of the B family of regulatory subunits of the protein phosphatase PP2A, as important modulators of TGF-β/Activin/Nodal signalling, which affect the pathway in opposite ways. Knockdown of Bα in Xenopus embryos or mammalian tissue culture cells suppresses TGF-β/Activin/Nodal-dependent responses, whereas knockdown of Bδ enhances these responses. Moreover, in Drosophila, overexpression of Smad2 rescues a severe wing phenotype caused by o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 51 publications
1
61
0
Order By: Relevance
“…By contrast, the Bα subunit of PP2A itself becomes phosphorylated upon binding to TRI (Griswold-Prenner et al, 1998). The function of B subunits in TGFβ signalling seems to be the stabilization of the receptor complex, as both the knockdown of Bα and overexpression of Bδ lead to degradation of the type-I receptor (Batut et al, 2008). Confirming the previous studies, we found an interaction between the PP2A-B subunits and TGFβ type-I and type-II receptors in vivo.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…By contrast, the Bα subunit of PP2A itself becomes phosphorylated upon binding to TRI (Griswold-Prenner et al, 1998). The function of B subunits in TGFβ signalling seems to be the stabilization of the receptor complex, as both the knockdown of Bα and overexpression of Bδ lead to degradation of the type-I receptor (Batut et al, 2008). Confirming the previous studies, we found an interaction between the PP2A-B subunits and TGFβ type-I and type-II receptors in vivo.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, the Bα and Bβ subunits of PP2A bind and become phosphorylated by TGFβRI (Griswold-Prenner et al, 1998). Most recently, Bα and Bδ have been shown to have opposite roles in TGFβ signalling: Bα activates the pathway by stabilizing Activin type-I receptor (ALK4) protein levels whereas Bδ represses the pathway by downregulating ALK4 activity (Batut et al, 2008). Finally, inhibition of PP2A enhances the C-terminal phosphorylation of TGFβ-Smads (Van Berlo et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…CDK8/9 have access to Smad molecules on the chromatin but not to receptor-activated Smad molecules that fail to engage in transcriptional complexes ). Another fate for activated Smads is C-terminal dephosphorylation, which mediates Smad recycling for new rounds of signaling and thereby links the duration of signaling to the presence of activated TGF-b or BMP receptors (Batut et al 2008;Schmierer et al 2008). However, Smad C-terminal dephosphorylation does not require prior participation of the molecule in transcription.…”
Section: Discussionmentioning
confidence: 99%
“…The PP2A phosphatase is also implicated in TGF-b receptor dephosphorylation. Interestingly, the related PP2A subunits Ba and Bd modulate TGF-b signaling in opposite ways; whereas the Ba subunit enhances TGF-b signaling, most likely by stabilizing TbRI, the Bd subunit suppresses TGF-b signaling, most likely by inhibiting the TbRI kinase activity (Griswold-Prenner et al 1998;Petritsch et al 2000;Batut et al 2008).…”
Section: Adam17mentioning
confidence: 99%